Retirement from trusteeship – Express and statutory powers: Supreme Court Case Summary: Chan Yun Cheong (trustee of the will of the testator) v Chan Chi Cheong (trustee of the will of the testator - CHAW, Noemi En-Hui Sarah (Institutional Knowledge at Singapore Management University, 2022)
This case involved two trustees of a testamentary trust,1 both of whom alleged that they had resigned as trustees. Trusteeship is a serious appointment that comes with responsibilities. Under the Trustees Act (Cap 337, 2005 Rev Ed) (“Trustees Act”), which governs trusts in Singapore, once a person takes up a trusteeship, he cannot simply relinquish his duties at will but must do so in accordance with the law and the terms of the trust instrument.